Novel Artificial 5′UTR Increase Modified mRNA Translation When Injected into Mouse Heart - Ann Anu Kurian; Matteo Ghiringhelli; Eyal Shalom; Gayatri Mainkar; Magdalena M. Żak; Matthew Adjmi; Jeffrey Downey; Seonghun Yoon; Nicole Dubois; Filip K. Swirski; Lior Zangi (Pharmaceutics)
Background/Objectives: Modified messenger RNA (modRNA) is a promising gene delivery method used to upregulate genes in cardiac tissue, with applications in both clinical and preclinical settings to prevent cardiac remodeling after ischemic injury. The 5′ untranslated region (5′UTR) plays a crucial role in regulating the translation efficiency of mRNA into functional proteins. Due to the high production cost and short half-life of modRNA, it is essential to identify novel 5′UTR designs that enhance modRNA translation in the heart. Methods: Here, we present an artificial 5′UTR, termed “Top Heart 5′UTR”, designed based on ribonucleotide frequency analyses of 1000 genes highly expressed in the heart. This novel artificial 5′UTR contains a unique 20-nucleotide sequence, consisting of 11 previously uncharacterized nucleotides (CCCCCGCCCCC) and 9 well-described nucleotides from the Kozak sequence upstream of the start codon (ATG). Results: This design significantly improves modRNA translation efficiency in cardiomyocytes (CMs) and heart cells both in vitro and in vivo. Specifically, the Top Heart 5′UTR increases translation efficiency by approximately 30–60% in both mouse and human CMs compared to a standard 5′UTR control. Moreover, the artificial 5′UTR induces a 2–2.5 times higher translation of modRNA in the mouse heart 24 and 48 h post-delivery. Conclusions: Our findings may contribute to the development of a superior modRNA platform for use in preclinical and clinical studies, potentially allowing reduced dosages or increased gene expression at the same dosage level. This approach can be extended to identify optimized 5′UTRs for various cell types or organs, including applications in cancer therapies.